Self-Healing Nanotextured Vascular-like Materials: Mode I Crack Propagation - Lee, Min Wook; Sett, Soumyadip; An, Seongpil; Yoon, Sam S.; Yarin, Alexander L. (American Chemical Society, 2017)
Here, we investigate crack propagation initiated from an initial notch in a self-healing material. The crack propagation in the core shell nanofiber mats formed by coelectrospinning and the composites reinforced by them is in focus. All samples are observed from the crack initiation until complete failure. Due to the short-time experiments done on purpose, the resin and cure released from the cores of the core shell nanofibers could not achieve a complete curing and stop crack, growth, especially given the fact that no heating was used. The aim is to elucidate their effect on the rate of crack propagation. The crack propagation speed in polyacrylonitrile (PAN) resin cure nanofiber mats (with PAN being the polymer in the shell) was remarkably lower than that in the corresponding monolithic PAN nanofiber mat, down to 10%. The nanofiber mats were also encased in polydimethylsiloxane (PDMS) matrix to form composites. The crack shape and propagation in the composite samples were studied experimentally and analyzed theoretically, and the theoretical results revealed agreement with the experimental data.
Keywords: CORE-SHELL NANOFIBERS; MECHANICAL-PROPERTIES; MICROVASCULAR NETWORKS; COMPOSITES; COATINGS; RELEASE; MATS